O processo tradutório na perspectiva da retextualização e sua abordagem no ensino de inglês como língua estrangeira - Castro, Mayelli Caldas de (2010)
This research aims mainly to reflect on the translation act as one of Retextualization. We will therefore discuss the activity of translation as a text (re)production, that is to say, a production of a new/same text that has as its source a different language. We will also attempt to identify and examine how the factors of textuality contribute to the translation process. By doing so, we hope to fulfill our main objective, which is: to analyze the relevance of the use of these translated texts in the English class and the importance of this approach in facilitating the comprehension of a text by the target readers, secondary students studying English as a foreign language. This translation approach relies on elements from textual linguistics because we cannot translate single words but texts. Thus, this is about text analysis, with its phases of production and, consequently, of co-production. In order to perform this analysis, a number of didactic texts, originally written in English and translated into Brazilian Portuguese, was selected. The pragmatic components to extend the analyses and factors of textualization proposed by Beaugrande and Dressler were also used as criteria of textuality. The main intention of this research is to investigate and to highlight which factors of textuality determine the choices made by the translator and how the choice of vocabulary can interfere in the function performed by these factors, so as to therefore better understand implications in teaching English as a foreign language.